The comparative effectiveness between automative and manual harvesting system / Mohamad Muizz Redzuan - Redzuan, Mohamad Muizz (Faculty of Plantation and Agrotechnology, 2016)
Harvesting is one of the most importance activity for producing the estate production. The productivity of oil palm is mostly depends on age of palm (cropping level), topography, and workers' skills. Meanwhile, the efficiency of the harvesting system can increase the productivity and profit of oil palm production. Abdul et al. (2008) found that the manual harvesting system theoretically can produce about 250 to 350 bunches and meanwhile the automated harvesting system theoretically can produce about 560 to 750 bunches. This study is comparing the efficiency of two types of harvesting system which are manual and automated (SmartCUT). In the end this study, it was found that the usage of the SmartCUT is more efficient than manual harvesting system in term of oil palm productivity and cost implication of oil palm production.